Analisis Kinerja Keuangan Dengan Menggunakan Metode Economic Value Added (EVA) Pada PT Campina Ice Cream Industry Tbk Periode 2017-2021 - Anggi Pebriyani; M. Imam Sundarta; R. Dudung Abdul Syukur (eCo-Fin, 2023)
PT Campina Ice Cream Industry Tbk is one of the food and beverage companies listed on the Indonesia Stock Exchange (IDX). The purpose of this study is to determine the financial performance of the company using the Economic Value Added (EVA) method. This type of research is descriptive qualitative, using financial statement data for 2017-2021 obtained from the company's official website and the IDX. The results of this study indicate that PT Campina Ice Cream Industry Tbk achieved a positive EVA value in 2017 and a negative EVA value in 2018-2021. A positive EVA value, or EVA > 0, means that the company is able to create added value, which indicates that the profit generated is able to cover the existing capital costs (Capital Charges), which means that the company is able to meet shareholders' expectations and the company's financial performance is said to be good. Conversely, a negative EVA value or EVA < 0, which means that the company has not been able to create value, indicates that the profit earned cannot cover the existing capital charges, which means that the company has not been able to meet the expectations of shareholders and the financial performance of the company is said to be not good.